2021
DOI: 10.1130/abs/2021am-365199
|View full text |Cite
|
Sign up to set email alerts
|

Arclogites in the Subarc Lower Crust: Effects of Crystallization, Partial Melting, and Retained Melt on the Foundering Ability of Residual Roots

Abstract: Thick-crusted (>45 km) Cordilleran arcs exhibit cyclic processes including periods of magmatic quiescence interspersed with pulses of high-flux magmatism. Most models assume that during high-flux events, fractional crystallization and partial melting within the deep crustal hot zone generate a dense (>3.4 g/cm 3 ) arclogitic subarc root that can readily founder into the mantle. Yet these models do not consider that: (1) the retention of low-density melt within the subarc root, and (2) the protolith lithology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 202 publications
(396 reference statements)
0
1
0
Order By: Relevance
“…(2002) showed that Moho can range from 35 to over 80 km deep in nearby areas of the Central Andes although in detail several surfaces can be identified as potential Moho discontinuities (Assumpção et al., 2013). The petrology of lower crustal domains under magmatic arcs is such that sizable masses of residual/cumulate pyroxenites are both required by models (Bowman et al., 2021) and observed in the few areas where old lower crustal sub‐arc domains are exposed at the surface (Kidder et al., 2003; Walker et al., 2015) as well as in the xenolith record (Ducea & Saleeby, 1998). These pyroxenites, with or without amphibole, garnet, magnetite/ilmenite, or plagioclase, cover a range of seismic velocities that can straddle the boundary between lower crust and upper mantle from granulite to arclogite (Ducea et al., 2021 and references therein).…”
Section: The Moho Discontinuitymentioning
confidence: 99%
“…(2002) showed that Moho can range from 35 to over 80 km deep in nearby areas of the Central Andes although in detail several surfaces can be identified as potential Moho discontinuities (Assumpção et al., 2013). The petrology of lower crustal domains under magmatic arcs is such that sizable masses of residual/cumulate pyroxenites are both required by models (Bowman et al., 2021) and observed in the few areas where old lower crustal sub‐arc domains are exposed at the surface (Kidder et al., 2003; Walker et al., 2015) as well as in the xenolith record (Ducea & Saleeby, 1998). These pyroxenites, with or without amphibole, garnet, magnetite/ilmenite, or plagioclase, cover a range of seismic velocities that can straddle the boundary between lower crust and upper mantle from granulite to arclogite (Ducea et al., 2021 and references therein).…”
Section: The Moho Discontinuitymentioning
confidence: 99%